2005
DOI: 10.4103/0255-0857.16591
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluorochrome stain in the diagnosis of pulmonary tuberculosis co-infected with HIV

Abstract: Fluorochrome staining was found to be more efficient (45%) when compared to ZN staining (29%) in detecting cases associated with HIV seropositivity, especially paucibacillary cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 3 publications
2
21
0
Order By: Relevance
“…Our results were similar with. Prasanti K, 9 Cheng AG, 10 Sethi S, 11 Singh NP, 12 Ulukanligil M, 13 and Jain A 14 in their studies which also found AR stain was more sensitive in comparison with ZN stain for the diagnosis of tubercular bacilli. Thus it is concluded that, for detection of AFB in paucibacillary specimen, AR is much more sensitive than ZN staining technique.…”
Section: Discussionmentioning
confidence: 90%
“…Our results were similar with. Prasanti K, 9 Cheng AG, 10 Sethi S, 11 Singh NP, 12 Ulukanligil M, 13 and Jain A 14 in their studies which also found AR stain was more sensitive in comparison with ZN stain for the diagnosis of tubercular bacilli. Thus it is concluded that, for detection of AFB in paucibacillary specimen, AR is much more sensitive than ZN staining technique.…”
Section: Discussionmentioning
confidence: 90%
“…staining, 32% by ZN staining). [6][7][8][9][10] The use of fluorescent stain greatly improves the diagnostic value of the EPTB smears with a low density of bacilli (Paucibacillary) which are likely to be missed on ZN stained smear. This study showed the higher isolation rate of MTB complex in MGIT culture system (96.29%) than the conventional LJ medium culture assay (81.48%).…”
Section: Resultsmentioning
confidence: 99%
“…Although smear microscopy is less frequently positive in patients infected with HIV and TB, advances in fluorescence microscopy (94)(95)(96)(97) and optimization of smear preparation (98)(99)(100)(101), coupled with important steps toward so-called frontloaded microscopy, in which two samples are taken on the same day (102), ensure that smear microscopy remains the mainstay of diagnosis of TB globally. However, new diagnostic tools for the detection of TB and drug-resistant TB have been developed on the basis of both phenotypic and genotypic methods.…”
Section: Active Tb Disease Diagnosis In Hivmentioning
confidence: 99%